Cycles de reproduction et exploitation des holothuries Aspidochirotes (Holothuroidea : Echinodermata) inféodées aux herbiers à Posidonia oceanica de la côte algéroise. - NEGHLI Larbi (My University, 2014)
Recently, special attention was given to Aspidochirotid holothurians colonizing Posidonia oceanica meadows of the Algerian coasts. Indeed, these macrofaunal detritic-feeders, commonly called "sea cucumber", belong to an essential compartment of a crucial Mediterranean ecosystem called “Posidonia oceanica meadow”. This study on the sexual reproduction of Aspidochirotid holothurians is part of a larger scientific project aiming to better understand some aspects of the biology and ecology of these animals as an essential part of the functioning of the Posidonia oceanica ecosystem. From the five Aspidochirotid species known to be enfeoffed to the Algerian seagrass, only three have been adequately sampled; Holothuria (H.) tubulosa GMELIN (1790), Holothuria (P.) sanctori DELLE CHIAJE (1823) and Holothuria (R.) poli DELLE CHIAJE (1823). The two other species Holothuria (H.) stellati and Holothuria (P.) forskali were much rarer at the sampling sites. For the needs of the present study, two sites were sampled, both located in the central part of the Algerian coast. The first one, relatively distant from human action, is located in "Berard" in the district of Tipaza and the second is located at "La Perouse" (Algiers) and is characterized by the influence of two major effluents; Oued El Harrach and Oued el Hamiz. Through this approach, it was possible to perform a comparative analysis of the effects of ecological and environmental parameters on the gamogenetic maturation and the physical condition of these primitive organisms. For this purpose, the LECREN condition index "Kn" and the gonado-somatic index "RGS" were compared using the two factors; sex and sampling site. Then the observed differences were statistically tested for their significance (Kruskal-Wallis non-parametric test and parametric test of WELCH). For the three studied species, the results showed a tendency to individual overweight for samples collected at Lapérouse area. The average differences in terms of relative biomass were about 40% higher for Holothuria (P.) sanctori, 26% for Holothuria (H.) tubulosa and 54% for Holothuria (R.) poli. For Holothuria (P.) sanctori which was the best-studied species (as the most provided in samples), comparison of the monthly average condition index Kn revealed no significant differences between males and females. Except at the spring period during which females had a relatively lower Kn compared to males. Studying evolution of the monthly RGS index allowed us to retrieve the major phases of gonadal development for the three species. Gametic maturation phase begins in winter and ended in summer season, followed by spawn that took place at the period of warmer sea (late August early September). Resting phase came just after with the cooling water period. Obtained results from the gonadal microscopic structures analysis showed differences in Holothuria (P.) sanctori reproductive behavior according to the factor “sampling location”. For samples from Bérard, analysis of ovarian structures indicates two episodes of females fry during the year 2011. The first spawning occurred in May and was only partial with just some eggs released and was followed by a second brood in late August to early September which saw the release of all ovarian products. On other side, females’ population of Lapérouse had only one known fry, preceded by a late maturation phase. In addition, our results showed that the ovarian maturation phase for Holothuria (P.) sanctori from Lapérouse was comparatively longer that of the Bérard population. For Holothuria (P.) forskali, the few specimens that we collected during March and April 2011 showed gonads at spawning stage or in advanced maturation stage. This allows us to place the fry period of the specie in the same months. These results confirm the specie predilection for cold waters as established for the East-Atlantic population. In the end, it is clear from this work that sexual reproduction of the three gonochoric species generally follows the same pattern already described for the majority of Aspidochirotid sea-cucumber from temperate zones. These animals also demonstrated their ability to adapt to environmental conditions and to take advantage of their status as suspension feeders of dead organic matter in a specific situation of ecological disturbances induced by urban loads.
Keywords: sea-cucumbers, Aspidochirotes, Reproduction, Gonado-somatic Ratio, Histology, Condition Index, pollution.